Актуальные проблемы здорового образа жизни молодежи - Ким, В.А.; Кац, Н.А.; Козлова, Л.И. (My University, 2013)
Since the health of the population – the highest national value, then the revival of nations must begin just with health, especially children. A man comes into this world, not only for their comfortable existence and happiness. His intelligence, skill, experience, his entire life are necessary to his children, to society, to future generations. Worthy of man's existence on earth helps make health, mental and physical, which is the main property rights. And the 397 work is not only personal, but also social. Health can not be considered as a lack of physical defects or diseases in humans. Constitution of the World Health Organization (WHO) interprets the term "health" as "a state of complete social and spiritual well-being." For a child to be healthy means to develop in harmony their physical and spiritual strength, stamina and balance to have, to be able to resist the action as environmental factors, as well as his inner world. Healthy way of life of the young generation is the guarantee of health of the nation as a whole. That is why it is necessary, and educational and training activities of the school in general and subject-teachers, class teachers in particular on health protection and promotion